2019
DOI: 10.1017/s0007114519001491
|View full text |Cite
|
Sign up to set email alerts
|

In vitrolipolysis and lymphatic absorption ofn-3 long-chain PUFA in the rat: influence of the molecular lipid species as carrier

Abstract: The aim of this work was to study the bioavailability of fatty acids (FA), focusing on n-3 long-chain (LC) PUFA, carried by different molecular lipid species, that is, phospholipids (PL) or TAG, with three formulations based on fish oils or marine PL, providing a similar n-3 LC PUFA amount. The digestive lipolysis was first assessed using an in vitro enzymatic model. Then, intestinal absorption and enterocyte metabolism were investigated in vivo, on male Wistar rats through lymph lipid analysis. The in vitro r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…The PL profile of the raw materials is given in Table 2. The two camelina press cakes did not have the same PL profile: a higher proportion of PC and a lower amount of PA were observed in press cake (2). The PL profile of press cake (2) was close to that of seeds described in the literature (79 mol % PC + PI, 5 mol % PA) [44].…”
Section: : Chemical Composition Of the Two Camelina Press Cakes And Of Scallop By-productssupporting
confidence: 51%
“…The PL profile of the raw materials is given in Table 2. The two camelina press cakes did not have the same PL profile: a higher proportion of PC and a lower amount of PA were observed in press cake (2). The PL profile of press cake (2) was close to that of seeds described in the literature (79 mol % PC + PI, 5 mol % PA) [44].…”
Section: : Chemical Composition Of the Two Camelina Press Cakes And Of Scallop By-productssupporting
confidence: 51%
“…Indeed, although recent data has described PL as potential preferential vectors of FA compared to TAG, notably concerning marine n-3 LC-PUFAs, [14][15][16][17] their capacity to increase systemic FA bioavailability remains controversial. [42,50] In this way, using a similar study design to the one employed here, but in piglets, Amate et al concluded that the bioavailability of n-3 LC PUFAs in lymph was unchanged, but that their distribution within lipoproteins was modulated, when provided as egg PL comparatively to marine TAG. [51] Nevertheless, the observed difference in plasma ALA abundance between RL and SL may result from differences in lipolysis and intestinal absorption rates.…”
Section: Discussionmentioning
confidence: 76%
“…Free FA were extracted according to the technique described by Bligh et Dyer. [40] PL and TAG were separated by thin layer chromatography (TLC), derived into FAME by transmethylation, [41,42] which were analyzed by GC-FID (Supplementary Experimental Section).…”
Section: Plasma and Hepatic Lipid Analysismentioning
confidence: 99%
“…Another critical liver-specific gene is the pyruvate kinase. It has a prominent role in the glycolysis pathway and strongly correlates with liver lipid metabolism and mitochondrial function (Liu et al, 2019) (Rydén & Arner, 2017;Sehl et al, 2019;Vackova et al, 2019). Therefore, the combination of severe diet restriction with KO or FO, used in our experiment, probably promotes overstimulation of lipolysis in fat depots, resulting in excessive release of free fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte lipolysis is activated, and free fatty acid delivery from adipose tissue to the liver is continuously provoked. Besides, several in vitro and in vivo experiments have demonstrated that PUFAs stimulate lipolysis in adipose tissue (Rydén & Arner, 2017; Sehl et al, 2019; Vackova et al, 2019). Therefore, the combination of severe diet restriction with KO or FO, used in our experiment, probably promotes overstimulation of lipolysis in fat depots, resulting in excessive release of free fatty acids.…”
Section: Discussionmentioning
confidence: 99%